Scheduling Tank Container Movements for Chemical Logistics - KARIMI, I. (Institutional Knowledge at Singapore Management University, 2004)
The scheduling of tank container movements for chemical logistics was discussed. An innovative, event based, 'pull' approach for the minimum-cost or the maximum-profit scheduling of the transport and cleaning of multi-product tank containers in global chemical logistics was also discussed. Key practical extensions such as alternate ship schedules, delivery time-windows, and inter-modal transport routes were also incorporated.